Role of the transcription regulator RpoN (sigma 54) in Enterococcus faecalis biofilm development, metabolism and virulence - Iyer, Vijayalakshmi Subramanian (Kansas State University, 2014)
Enterococci are the third leading cause of nosocomial infections including urinary tract infections (UTI), surgical site infections (SSI) and blood stream infections. Enterococci are also found in the gastrointestinal tracts of humans, and other mammals. We elucidated the influence of the transcriptional regulator RpoN on enterococcal biofilm formation, virulence potential and cell wall architecture and proposed a potential involvement for carbohydrate metabolism in these processes. Biofilms are held together by matrix (BM) components such as extracellular DNA (eDNA) released by cell death from a sub-population of cells. The rpoN mutant (ΔrpoN) was resistant to autolysis as well as fratricide-mediated cell death and eDNA was not detected in planktonic as well as biofilm cultures. Unlike the parental strain V583, the ΔrpoN mutant formed proteinase K sensitive biofilms, suggesting that protein as well as eDNA serves as an important matrix component. The rabbit model of endocarditis was used to assess the effect of rpoN deletion on enterococcal virulence. Rabbits infected with ΔrpoN had reduced bacterial burden in heart, blood, liver, kidney and vegetation in comparison to the parental strain. The growth defect of ΔrpoN in physiologically relevant glucose levels (5 mM) partially explains the reduced bacterial burdens observed in the virulence study. Microarray analysis of ΔrpoN showed that 10% of the genome is differentially regulated by RpoN. Deletion of rpoN also protects Enterococcus faecalis from lysis in the absence of known modulators of cellular lytic events such as O-acetylation and D-alanylation. Of the four identified enhancer binding proteins in E. faecalis, MptR regulates the RpoN-dependent mannose/glucose uptake system (MptABCD) and the ΔmptR mutant phenocopied the ΔrpoN mutant in the eDNA release and growth assays. Because MptC and MptD have been shown to be the cellular receptors for class IIa and IIc bacteriocins, we are presently testing the hypothesis that these receptors may serve as a global receptor for bacteriocins. In conclusion, our data demonstrates that alterations in the metabolic state of the bacterium, as observed in the ΔrpoN mutant could be responsible for the switch in biofilm matrix composition, and this switch in turn likely influences the virulence potential of the bacterium.
Keywords: Transcription regulator; Enterococcus feacalis; RpoN; Biofilm; Microbiology (0410)